Cryopreservation of testis tissues and in vitro spermatogenesis. (5th August 2015) - Yokonishi, Tetsuhiro; Ogawa, Takehiko
Abstract: Cancer treatments, either chemo‐ or radiotherapy, may cause severe damage to gonads which could lead to the infertility of patients. In post‐pubertal male patients, semen cryopreservation is recommended to preserve the potential to have their own biological children in the future; however, it is not applicable to prepubertals. The preservation of testis tissue which contains spermatogonial stem cells (SSCs) but not sperm would be an alternative measure. The tissues or SSCs have to be transplanted back into patients to obtain sperm; however, this procedure remains experimental, invasive, and is accompanied with the potential risk of re‐implantation of cancer cells. Recently, we developed an organ culture system which supports the spermatogenesis of mice up to sperm formation from SSCs. It was also shown that the tissues could be frozen for later sperm production, which resulted in the generation of offspring. Thus, it could be useful as a clinical application for preserving the reproductive potential of male pediatric cancer patients. The establishment of an optimized cryopreservation method and the development of a culture system for human testis tissue are expected in the future.